1983
DOI: 10.1055/s-1983-30301
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Ethers

Abstract: B. The mechanism of the cleavage of ethers by anhydrous hydrogen halides.. . C. Further descriptive chemistry of cleavage by hydrogen halides.. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
185
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(192 citation statements)
references
References 83 publications
4
185
1
2
Order By: Relevance
“…Cyanates may adhere to a variety of substrates, e.g. metals, glass and carbon fibres and cyanate adhesives have yielded values of [14][15][16][17][18][19][20] MPa (for lap shear strength) on 20224 T-3 aluminium alloy (some 50-100% higher than corresponding BADGE and TGDDM epoxy adhesives (cured with aromatic diamines), but it is their behaviour on silicon that is of particular interest in the microelectronics arena because of the ubiquity of this material in the formation of MCMs. Typically, the latter are formed from sequentially built layers of metallised conductors on ceramic or silicon substrates and unreinforced polymer dielectric films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanates may adhere to a variety of substrates, e.g. metals, glass and carbon fibres and cyanate adhesives have yielded values of [14][15][16][17][18][19][20] MPa (for lap shear strength) on 20224 T-3 aluminium alloy (some 50-100% higher than corresponding BADGE and TGDDM epoxy adhesives (cured with aromatic diamines), but it is their behaviour on silicon that is of particular interest in the microelectronics arena because of the ubiquity of this material in the formation of MCMs. Typically, the latter are formed from sequentially built layers of metallised conductors on ceramic or silicon substrates and unreinforced polymer dielectric films.…”
Section: Introductionmentioning
confidence: 99%
“…For example, having produced (bis-4-(4-methoxyphenoxy) phenylethoxyethane from dichloroethane in high yield and purity (with the intention of cleaving the methyl ether to yield the diphenol prior to cyanation), it was not possible to deprotect this group using e.g. recognised methods such as boron tribromide [17] without breaking the alkylene ether backbone.…”
Section: Introductionmentioning
confidence: 99%
“…The methyl ether of 13c,d is cleaved without epimerization using boron tribromide (30). Analysis of the product by 'H and ' H nmr spectroscopy showed that the dideuterated 2S,3~-[2,3-'H~] serine (14c) and the trideuterated 2s-[2,3,3-'H3] serine ( 1 4 4 are formed in a 2:3 ratio by the hydrogenation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, demethylation of 22c occurred in a stepwise manner, and p-methoxyphenol was isolated. 25,26 3.3 Deprotection of alkyl aryl ethers AlI 3 was applied in deprotection of phenolic ethers to afford several phenol intermediates, as depicted in scheme 2. Demethylation of 24 with AlI 3 afforded 2-formyl-6-naphthol (25) in almost quantitative yield (Scheme 2A).…”
Section: Solvent Effectsmentioning
confidence: 99%